2011
DOI: 10.1016/j.ijpsycho.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate reactivity is associated with future cognitive ability and cognitive change in a large community sample

Abstract: The relationship between cardiovascular reactions to acute mental challenge in the laboratory and cognitive ability has received scant attention. The present study examined the association between reactivity and future cognitive ability. Heart rate and blood pressure reactions to a mental stress task were measured in 1647 participants comprising three distinct age cohorts. Cognitive ability was assessed using the Alice Heim-4 test of general intelligence and choice reaction time five and 12 years later. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 60 publications
7
39
0
Order By: Relevance
“…Blunted reactivity has been linked to a number of disorders and psychological states associated with deficits in emotional and motivational regulation such as depressive symptomatology (Carroll et al, 2007), disordered eating (Ginty et al, 2012), obesity (Carroll et al, 2008), and risk for addiction (Lovallo, 2007; Panknin et al, 2002). Further, blunted reactivity has been associated with a number of conditions that are associated with poor health including fibromyalgia (Reyes del Paso et al, 2010), fatigue (Peckerman et al, 2000), racial/ethnic discrimination (Salomon and Jagusztyn, 2008) and low cognitive ability (Ginty et al, 2011). Our findings provide some tentative support for motivational dysregulation in depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blunted reactivity has been linked to a number of disorders and psychological states associated with deficits in emotional and motivational regulation such as depressive symptomatology (Carroll et al, 2007), disordered eating (Ginty et al, 2012), obesity (Carroll et al, 2008), and risk for addiction (Lovallo, 2007; Panknin et al, 2002). Further, blunted reactivity has been associated with a number of conditions that are associated with poor health including fibromyalgia (Reyes del Paso et al, 2010), fatigue (Peckerman et al, 2000), racial/ethnic discrimination (Salomon and Jagusztyn, 2008) and low cognitive ability (Ginty et al, 2011). Our findings provide some tentative support for motivational dysregulation in depression.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, reactivity above or below the average range may indicate poor health. This argument is based on emerging evidence that comparably low levels of reactivity in both the cardiovascular and HPA systems are related to a number of unhealthy states including obesity (Carroll et al, 2008), addiction (al'Absi et al, 2003; Panknin et al, 2002), disordered eating behavior (Ginty et al, 2012), exercise dependence (Heaney et al, 2011), fibromyalgia (Reyes del Paso et al, 2010) and fatigue among Veterans with Gulf War Illness (Peckerman et al, 2000), as well as states that confer risk for poor health such as racial/ethnic discrimination (Salomon and Jagusztyn, 2008) and low cognitive ability (Ginty et al, 2011). Further, curvilinear relationships between physiological and psychological phenomenon is not without precedent.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a prospective cohort study in Scotland, lower CVR was a risk factor predicting future decline in reasoning and reaction time, and the relationship was stronger in old age relative to young and middle age groups (9). Reasoning, attention, and reaction time are components of executive function, which is a higher order cognitive system controlling multiple cognitive processes that regulate goal-directed behaviors and information organization (10).…”
Section: Introductionmentioning
confidence: 96%
“…The acute stressors used in the study were a series of acute laboratory-based mental stress tasks including a mental arithmetic task (Math) and a Stroop word-color task (Stroop). Executive function was assessed by five cognitive tests sharing different executive components, and independent of the acute mental stress tasks, allowing for a more comprehensive assessment of executive function (9). We tested the following hypotheses: (1) greater CVR to the acute mental stress tasks is associated with better executive function; and (2) the association between CVR and executive function is moderated by the frequency of engagement in MSA.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that low cognitive ability and slow RT were significant predictors of blunted heart rate stress reactivity after accounting for covariates including sociodemographics and medication use. In further analyses using a different age cohort (Ginty et al, 2011b), lower heart rate responses to acute stress were associated with slower RT at 5‐ and 12‐year follow‐up independent of covariates including baseline heart rate, socioeconomic position, and cohort type. Blood pressure responses to acute stress were not associated with RT in either study.…”
mentioning
confidence: 92%